Headspace solid phase microextraction in the analysis of pesticide residues – kinetics and quantification prior to the attainment of partition equilibrium - DRAGAN MARKOVIC; MIRJANA MARKOVIC; RADA DJUROVIC (Journal of the Serbian Chemical Society, 2007)
A new theoretical approach to the headspace/solid phase microextraction (HS/SPME) process is proposed and tested by the analysis of pesticide residues of water samples. The new approach focuses on mass transfer at the sample/gas phase and gas phase/SPME polymer interfaces. The presented model provides a directly proportional relationship between the amount of analytes sorbed by the SPME fiber and their initial concentrations in the sample. Also, the expression indicates that quantification is possible before partition equilibrium is attained. Experimental data for pesticides belonging to various classes of organic compounds were successfully interpreted by the developed model. Additionally, a linear dependence of the amount of pesticide sorbed on the initial analyte concentration in aqueous solution was obtained for a sampling time shorter than that required to reach sorption equilibrium.